69.9k views
2 votes
Solve -6(4-x)≤-4(x+1) for x
No silly answers please.

2 Answers

3 votes

Answer:

x ≤ 2

Explanation:

well, -6 x 4 = -24

-6 x X = -6x

so far, we have -24 -6x ≤-4(x+1)

-4 x X = -4x

and -4 x 1 = -4 , so we now have -24 -6x ≤ -4x + -4

now we subtract x on one side, and to the other side as well, and you do the same for the numbers!

User Ethan Choi
by
4.3k points
7 votes

Answer:

x≤2

Explanation:

User Jon Mountjoy
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.